Biodegradable iron oxide nanoparticles for intraoperative parathyroid gland imaging in thyroidectomy. Issue 3 (11th June 2022) - Zheng, Weihui; Liu, Chun; Jin, Jiaoyue; Sun, Wei; Zhao, Jianqiang; Zhao, Ming; Yao, Shili; Zhu, Bing; Chen, Fan; Shang, Jinbiao; Wang, Kejing; Guo, Peng; et al.
Abstract: Parathyroid gland (PG) injury is the most common complication of thyroidectomy owing to the lack of approaches for surgeons to effectively distinguish PGs from surrounding thyroid glands (TGs) in the operation room. Herein, we report the development of biodegradable iron oxide nanoparticles (IONPs) as a promising contrast agent candidate for intraoperative PG visualization. We elucidated that locally administrated dark-colored IONPs readily diffuse in TGs but cannot infiltrate tissue-dense PGs, yielding a distinguishable contrast enhancement between PGs and TGs by naked eye observation. We performed unbiased and quantitative in vivo screenings to optimize particle size and concentration of IONPs for PG/TG contrast enhancement. Moreover, in vivo applications of IONPs via the local administration route demonstrate no adverse toxicities and can be biodegraded in the thyroid microenvironment within 3 months. To our knowledge, these promising findings provide the first in vivo evidence that IONPs can serve as a safe, biodegradable, and effective contrast agent candidate for improving PG visualization in thyroidectomy.